Temperature effect on leaf water deuterium enrichment and isotopic fractionation during leaf lipid biosynthesis: Results from controlled growth of C3 and C4 land plants - Zhou, Youping; Grice, Kliti; Chikaraishi, Y.; Stuart-Williams, H.; Farquhar, G.; Ohkouchi, N. (elsevier, 2011)
The hydrogen isotopic ratios (2H/1H) of land plant leaf water and the carbon-bound hydrogen of leaf waxlipids are valuable indicators for climatic, physiological, metabolic and geochemical studies. Temperature will exert a profound effect on the stable isotopic composition of leaf water and leaf lipids as it directly influences the isotopic equilibrium (IE) during leaf water evaporation and cellular water dissociation. It is also expected to affect the kinetics of enzymes involved in lipid biosynthesis, and therefore the balance of hydrogen inputs along different biochemical routes. We conducted a controlled growth experiment to examine the effect of temperature on the stable hydrogen isotopic composition of leaf water and the biological and biochemical isotopic fractionations during lipid biosynthesis. We find that leaf water 2H enrichment at 20 C is lower than that at 30 C. This is contrary to the expectation that at lower temperatures leaf water should be more enriched in 2H due to a larger equilibrium isotope effect associated with evapotranspiration from the leaf if all other variables are held constant.A hypothesis is presented to explain the apparent discrepancy whereby lower temperature-induced down-regulation of available aquaporin water channels and/or partial closure of transmembrane water channel forces water flow to “detour” to a more convoluted apoplastic pathway, effectively increasing the length over which diffusion acts against advection as described by the Péclet effect (Farquhar and Lloyd, 1993) and decreasing the average leaf water enrichment. The impact of temperature on leaf water enrichment is not reflected in the biological isotopic fractionation or the biochemical isotopic fractionation during lipid biosynthesis. Neither the biological nor biochemical fractionations at 20 C are significantly different from that at 30 C, implying that temperature has a negligible effect on the isotopic fractionation during lipid biosynthesis.